Educational Chatbot Based on Educational Technology in Improving Student Understanding of Algorithms and Programming Courses - Aniek Suryanti Kusuma; Anak Agung Gde Ekayana; Desak Made Dwi Utami Putra (Jurnal Edutech Undiksha, 2025)
The advancement of educational technology has driven the integration of Artificial Intelligence (AI) into learning processes; however, Algorithm and Programming courses remain challenging for students due to their abstract nature and the demands of logical thinking and problem-solving skills. This study aims to develop and evaluate the effectiveness of an AI-based educational chatbot in improving students’ understanding and engagement. The research employed an experimental method with a pre-test and post-test design involving two classes of students as research subjects. Data were collected through achievement tests designed to measure conceptual understanding, algorithmic thinking, and problem-solving abilities. Data analysis was conducted using paired sample t-tests to examine differences in learning outcomes and N-Gain analysis to determine the level of learning effectiveness. The results indicate a significant improvement in students’ learning outcomes after the use of the chatbot, with learning gains categorized as high in both groups. These findings demonstrate that AI-based chatbots are effective in enhancing conceptual understanding, algorithmic thinking skills, and student motivation. Therefore, educational chatbots have important implications as innovative solutions for creating adaptive, interactive, and student-centered learning environments in higher education.